IMPULSIVITAS SISWA SEKOLAH MENENGAH: PERAN MINDFULNESS DAN SELF-CONTROL - Nurida, Ulfa; Widyasari, Pratiwi (Program Studi Psikologi Universitas Pendidikan Indonesia, 2020)
This research aims to determine the psychometric properties of MDS3 (Marylands Safety and Supportive School) school climate measurement tools which are adapted in Indonesian to high school students. The study participants consisted of 200 public and private high school students in Bandung. The MDS3 instrument in the English version translated into Indonesian consists of 56 items that have three dimensions namely Safety, Engagement and Environment. Psychometric analyzes such as item-total correlation, Alpha reliability, and exploratory factor analysis were performed as empirical evidence of the psychometric quality of this instrument. The results of this study indicated that the reliability of this instrument is high, 0.881 with item discrimination power or total-item correlations that are relatively weak in the Safety Dimension. Exploratory factor analysis also showed unsatisfactory results on the Safety dimension because many items are different from the model of the factor structure of school climate measurement tools. The lack of fit models used in factor analysis could be due to inadequate or insufficient samples because only at state high schools, while only one respondent came from private high schools. Adding samples and repairing items needs to be done to improve the quality of the Indonesian version of the MDS3.